A Strategic Study on Cultivating Craftsman Spirit Based on Enhancing the Core Competitiveness of Private Enterprises - Liu, Shuyan; Liu, Zhuochen (Journal of Social Science and Humanities, 2024)
In the ever-changing market environment, the competitive pressure on private enterprises is increasing. The integration of craftsmanship provides strong support for private enterprises to shape unique competitive advantages and enhance core competitiveness. This paper analyzes the connotation and value of craftsmanship, emphasizes its key role in enhancing the core competitiveness of private enterprises, and comprehensively examines the current status and problems of cultivating craftsmanship in private enterprises, and points out the shortcomings. On this basis, a strategy for cultivating craftsmanship based on enhancing the core competitiveness of private enterprises is proposed.